Correction of Mutant p63 in EEC Syndrome Using siRNA Mediated Allele‐Specific Silencing Restores Defective Stem Cell Function. (16th March 2016) - Barbaro, Vanessa; Nasti, Annamaria A.; Del Vecchio, Claudia; Ferrari, Stefano; Migliorati, Angelo; Raffa, Paolo; Lariccia, Vincenzo; Nespeca, Patrizia; Biasolo, Mariangela; Willoughby, Colin E.; Ponzin, Diego; Palù, Giorgio; et al.
Abstract : Ectrodactyly‐Ectodermal dysplasia‐Clefting (EEC) syndrome is a rare autosomal dominant disease caused by heterozygous mutations in the p63 gene and characterized by limb defects, orofacial clefting, ectodermal dysplasia, and ocular defects. Patients develop progressive total bilateral limbal stem cell deficiency, which eventually results in corneal blindness. Medical and surgical treatments are ineffective and of limited benefit. Oral mucosa epithelial stem cells (OMESCs) represent an alternative source of stem cells capable of regenerating the corneal epithelium and, combined with gene therapy, could provide an attractive therapeutic avenue. OMESCs from EEC patients carrying the most severe p63 mutations (p.R279H and p.R304Q) were characterized and the genetic defect of p.R279H silenced using allele‐specific (AS) small interfering RNAs (siRNAs). Systematic screening of locked nucleic acid (LNA)‐siRNAs against R279H‐p63 allele in (i) stable WT‐ΔNp63α‐RFP and R279H‐ΔNp63α‐EGFP cell lines, (ii) transient doubly transfected cell lines, and (iii) p.R279H OMESCs, identified a number of potent siRNA inhibitors for the mutant allele, which had no effect on wild‐type p63. In addition, siRNA treatment led to longer acquired life span of mutated stem cells compared to controls, less accelerated stem cell differentiation in vitro, reduced proliferation properties, and effective ability in correcting the epithelial hypoplasia, thus giving rise to full thickness stratified and differentiated epithelia. This study demonstrates the phenotypic correction of mutant stem cells (OMESCs) in EEC syndrome by means of siRNA mediated AS silencing with restoration of function. The application of siRNA, alone or in combination with cell‐based therapies, offers a therapeutic strategy for corneal blindness in EEC syndrome. Stem Cells 2016;34:1588–1600